The Arabidopsis Cyclophilin Gene Family - Romano, Patrick G.N. (American Society of Plant Biologists, 2004)
Database searching has allowed the identification of a number of previously unreported single and multidomain isoform members of the Arabidopsis cyclophilin gene family. In addition to the cyclophilin-like peptidyl-prolyl cis-trans isomerase domain, the latter contain a variety of other domains with characterized functions. Transcriptional analysis showed they are expressed throughout the plant, and different isoforms are present in all parts of the cell including the cytosol, nucleus, mitochondria, secretory pathway, and chloroplast. The abundance and diversity of cyclophilin isoforms suggests that, like their animal counterparts, plant cyclophilins are likely to be important proteins involved in a wide variety of cellular processes. As well as fulfilling the basic role of protein folding, they may also play important roles in mRNA processing, protein degradation, and signal transduction and thus may be crucial during both development and stress responsiveness.